KARAKTERISTIK PENDERITA PENYAKIT PARU OBSTRUKSI KRONIK (PPOK) YANG DIRAWAT INAP DI RSUP H. ADAM MALIK MEDAN TAHUN 2012 - Panamotan Sidabutar; Rasmaliah ,MKes; Hiswani ,MKes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Chronic Obstructive Pulmonary Disease (COPD) is a disease characterized by continuous and progressive airflow resistance and is usually associated with increased chronic inflammatory response to noxious particles and gases in the respiratory tract. The high proportion of smokers in Indonesia is 65.9% of the male population aged and 4.2% of women above 15 years old and the use of cigarettes are too early to describe COPD. To determine the characteristics of patients with COPD who are hospitalized in H. Adam Malik Hospital Medan, conducted research by using a case series design. Population and the samples were 110 patients in 2012, were recorded in hospital medical records. Univariate data was analyzed descriptively while bivariate data was analyzed by using Chi-square test, Mann-Whitney and Kruskal Wallis with 95% CI. Based on socio-demographic, the highest proportions were in the age group ≥ 60 years (64.5%), male gender (86.5%), 56.4% Protestant religion, level of education high school / equivalent (61.8%), retired job (36.4%), and the outsider of Medan city (67.3%). Highest proportion based on the medical conditions were shortness of breath (100%), mild severity stage (50%), the last type of disease and hypertension pulmonary TB (28.4%), exacerbation of complications (63.1%), and history of smoking (70, 9%). The length Maintainability was on average 7.44 days, it was not their own cost but it was cost source (84.5%), while the condition by outpatient treatment (77.3%). There is a significant difference between the cost of a long treatment with source (p = 0.001) and the condition after going out of being hospitalized (p = 0.001). There is no significant difference between smoking history based on complications and duration of treatment based on complications. The hospital are expected to complete the registration card status and continuing education programs for the patients and the families of patients, and to the patients are expected to reduce exposure to COPD risk factors. Keywords: COPD, patient characteristics